A construction of service-oriented architecture adoption maturity levels using adoption of innovation concept and CMMI - Hamzah, Mohd Hamdi Irwan; Baharom, Fauziah; Mohd, Haslina; Omar, Mohd Hasbullah (Universiti Teknikal Malaysia Melaka, 2018)
The existing Service-Oriented Architecture (SOA) maturity models constructed their maturity level focuses on the level after the implementation of SOA in the organization. However, less work has been carried out regarding the SOA maturity level that focused on the whole process of SOA adoption including the pre-adoption level. Furthermore, this study also found that less work on constructing the maturity levels for measuring the SOA adoption existed. Therefore, this study aims to construct the Service-Oriented Architecture adoption maturity level by combining the adoption of innovation concept with Capability Maturity Model Integration (CMMI). This study constructs the lower level of the proposed SOA adoption maturity level based on the adoption of innovation concept and the upper level based on CMMI and the existing SOA maturity models. This study has successfully shown that the adoption of innovation concept can be combined with CMMI in order to construct a holistic maturity level for evaluating the SOA adoption. This level covers the whole SOA adoption processes ranging from the pre-adoption level up to the optimized level. This study also aims at evaluating the SOA adoption toward sustainable development. Sustainable development means that the teams work at consistence and continuous speed to produce a quality result. Thus, the proposed maturity level may benefit the SOA practitioner and software quality assurance in software engineering domain.